Social change for women and children - Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (JAI Press, 2000)
The contributors to this volume consider policy implications of gender research with an emphasis on its relevance for children - particularly girls; and gender inequality within a range of contexts from that of Cameroon society where basic education is an issue, to that of feminist family settings in the United States.
Keywords: Social change -- United States.; Women -- United States -- Social conditions.; Women -- Latin America -- Social conditions.; Children -- Social conditions.; Gender studies, gender groups.; Social research & statistics.; Social Science -- Gender Studies.; elektronické knihy; electronic books